The phonology of tone and intonation - Gussenhoven, Carlos (Cambridge : Cambridge University Press, 2004)
Tone and Intonation are two types of pitch variation, which are used to give shape to utterances. In this book, Carlos Gussenhoven provides an up-to-date survey of research into tone and intonation, discussing why speakers vary their pitch, what pitch variations mean, and how they are integrated into our grammars.
Includes references and index.
Keywords: Tone (Phonetics).; Grammar, Comparative and general -- Phonology